A USB-controlled potentiostat/galvanostat for thin-film battery characterization. (October 2017) - Dobbelaere, Thomas; Vereecken, Philippe M.; Detavernier, Christophe
Graphical abstract: Abstract: This article describes the design of a low-cost USB-controlled potentiostat/galvanostat which can measure or apply potentials in the range of ±8 V, and measure or apply currents ranging from nanoamps to max. ±25 mA. Precision is excellent thanks to the on-board 20-bit D/A-convertor and 22-bit A/D-convertors. The dual control modes and its wide potential range make it especially suitable for battery characterization. As an example use case, measurements are presented on a lithium-ion test cell using thin-film anatase TiO2 as the working electrode. A cross-platform Python program may be used to run electrochemical experiments within an easy-to-use graphical user interface. Designed with an open hardware philosophy and using open-source tools, all the details of the project (including the schematic, PCB design, microcontroller firmware, and host computer software) are freely available, making custom modifications of the design straightforward.